Answer:
x=-36
Explanation:
Add the 7/2x +1/2x to be 8/2x which means that it'll be 4x=18=9/2
then subtract 9/2x on both sides so itll be
![4x=18+(9)/(2) x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fymby0nn8ja2zypo556wsp59f8ea11kcsh.png)
-9/2x -9/2x
because if you do 8/2-9/2 it's -1/2
then multiply the reciprocal to both sides so
![((2)/(-1))(-(1)/(2)x)=((2)/(-1))(18)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ojm7bhxn7jqhbsfdysqem3kgaoicugo01o.png)
which then cancels out -1/2 and makes it
x=-36